2005
DOI: 10.1254/jphs.fp0040603
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Human Liver Microsomes to Explain Individual Differences in Paclitaxel Metabolism by CYP2C8 and CYP3A4

Abstract: Abstract. Paclitaxel is widely used for treatment of malignant tumors. Paclitaxel is metabolized by CYP2C8 and CYP3A4, and these enzymes are known to differ between individuals, although the details have not been clarified. Recent progress in pharmacogenetics has shown that genetic polymorphisms of metabolic enzymes are related to these individual differences. We investigated the effect of the polymorphisms on paclitaxel metabolism by analyzing metabolic activities of CYP2C8 and CYP3A4 and expressions of mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 11 publications
(9 reference statements)
2
45
0
Order By: Relevance
“…In our present study, the formation of 6a-hydroxypaclitaxel was about 9 times higher than that of p-39-hydroxypaclitaxel based on the observed V max /K m ratio, indicating that CYP2C8-mediated paclitaxel hydroxylation was more predominant in the current batch of HLMs. The predominance of 6a-hydroxypaclitaxel formation, up to 13-fold higher as compared with p-39-hydroxypaclitaxel, was also observed in some individual livers (Václavíková et al, 2003;Taniguchi et al, 2005). In vivo, the level of 6a-hydroxypaclitaxel was about 4 times higher than that of p-39-hydroxypaclitaxel in bile and urine samples, suggesting that CYP2C8 played a major role in paclitaxel metabolism in human (Monsarrat et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our present study, the formation of 6a-hydroxypaclitaxel was about 9 times higher than that of p-39-hydroxypaclitaxel based on the observed V max /K m ratio, indicating that CYP2C8-mediated paclitaxel hydroxylation was more predominant in the current batch of HLMs. The predominance of 6a-hydroxypaclitaxel formation, up to 13-fold higher as compared with p-39-hydroxypaclitaxel, was also observed in some individual livers (Václavíková et al, 2003;Taniguchi et al, 2005). In vivo, the level of 6a-hydroxypaclitaxel was about 4 times higher than that of p-39-hydroxypaclitaxel in bile and urine samples, suggesting that CYP2C8 played a major role in paclitaxel metabolism in human (Monsarrat et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…In human bile samples, 6a-hydroxypaclitaxel (;13% of the dose) is about 4-fold higher than p-39-hydroxypaclitaxel (;3% of the dose), suggesting that CYP2C8 plays a major role in the metabolic clearance of paclitaxel in vivo (Monsarrat et al, 1993(Monsarrat et al, , 1998. In human liver microsomes (HLMs), it has been reported that levels of 6a-hydroxypaclitaxel are consistently higher (;2.3-fold) than those of p-39-hydroxypaclitaxel (Taniguchi et al, 2005), while a more extensive study using 47 individual HLMs showed that CYP3A4-mediated paclitaxel p-39-hydroxylation could be more predominant in subjects receiving phenobarbital treatment (Sonnichsen et al, 1995). In addition to cytochrome P450 (P450)-mediated metabolic clearance, efflux transport mediated by P-glycoprotein (P-gp) may play a role in paclitaxel disposition (Sparreboom et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…34 One recent study in ovarian cancer identified an association between ABCB1 2677G4A/T and response to paclitaxel in 53 Swedish ovarian cancer patients, 35 but this could not be replicated in a larger ovarian cancer study, 36 and was not seen in the breast cancer patients in this study. Although in vitro evidence suggests a role for CYP2C8 and CYP3A4 in paclitaxel metabolism, 4,5 it is possible that other variables such as epigenetic regulation mask these effects in vivo. For example, the nuclear receptor, NR1I2 has been shown to regulate paclitaxel metabolism and efflux, 37 and methylation status in ovarian tumor has been associated with response to taxane therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Data from liver microsomes demonstrate that CYP2C8 and CYP3A4 are primarily responsible for paclitaxel metabolism, 4,5 with CYP2C8 demonstrating a 2.3-fold greater metabolite production than CYP3A4. 5 The CY2C8*3 variant allele has been associated with decreased paclitaxel 6 a-hydroxylase activity in human cell lines and human liver microsomes. 4,6 Functional variants in the CYP3A gene family have been identified that could potentially impact drug metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…As the formation of 6a-hydroxypaclitaxel, approximately 30 times less toxic than the parent compound (Harris et al, 1994), has been shown to be the primary metabolic pathway of paclitaxel metabolism (Taniguchi et al, 2005), it would be reasonable to hypothesize that CYP2C8 polymorphisms could influence the efficacy of paclitaxel treatment. This question has been dealt with by Nakajima et al (2005), who found a 16-fold interindividual variation in the 6a-hydroxypaclitaxel area under the curve (AUC) among 23 female ovarian cancer patients, but apparently no CYP2C8 variant alleles, due to the small study or low frequency of the alleles in Japanese.…”
Section: Cyp2csmentioning
confidence: 99%